The Impact of Training and Development on College Instructors’ Professional Development at St. Cecilia's College-Cebu, Inc. - Niña Alexis S. Trinidad; Rhea Mae L. Cabornay; Jane Teñedo; Cristine Kay L. Bolo; Mark Anthony N. Polinar; Nerissa M. Auxilio; Ma. Elaijahbeth Z. Entia; Mary Joy I. Sadio; Mary Glennda Fajardo (Future Science / FSH-PH Publications, 2026)
This descriptive-correlational study investigated the effect of training and development programs on the professional development of college instructors at St. Cecilia College-Cebu, Inc., through identifying the direct impacts of the training and development variables on their professional development. A survey questionnaire was used to gather data from 33 college instructors. To analyse the data, both descriptive and inferential statistics were applied, specifically Spearman's Rho correlation and Multiple Regression. The results confirmed significant positive correlations between training method (Spearman’s ρ=.613, p <.001), training frequency (Spearman's ρ =.547, p =.002), trainer expertise (Spearman's ρ =.567, p <.001), training resources (Spearman’s ρ =.620, p <.001), and professional development. A multiple regression analysis indicated that the four predictors jointly accounted for 56.7% of the variance in professional development (R² = 0.567). Expertise of trainers (β = .402) and training resources (β = .351) were the strongest predictors. The other predictors, including training method (β = 0.298) and training frequency (β= 0.276), were also significant (β= 0.276). These findings highlight the importance of proper training strategies, continuous training, professional facilitation, and adequate resources in promoting professional development. Finally, the institution should improve its training and development processes by adopting more interactive and practical methods, such as blended learning and scenario-based training. The institution should also invest in trainers' continuous development through regular appraisals and professional development opportunities. The training session plan needs to be more consistent and comprehensive to support routine professional development.